Membangun Generasi Tanggap Bencana: Edukasi dan Kesiapan Siswa - Suratmin, Suratmin; Purnomo, Julyan; Faisal, M.Hanif; Kurnila, Nely; Kamil, Firmanilah; Ravi, Ahmad; Aida, Nur; Harahap, Saima Putrini R; Muttaqin, Khairul; Iswandi, Agung; Kalsum, Syf Umi; Putranto, Alan; Mastura, Syf (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2025)
Indonesia is a country with a high risk of natural disasters, due to its position between major tectonic plates and in the Pacific Ring of Fire. This condition makes Indonesia prone to disasters. However, the low level of student understanding of disaster response measures shows the importance of disaster education from an early age. This community service activity aims to improve the understanding and preparedness of SMKN 1 Ketapang students in facing disasters through socialization and simulation of disaster management. The activity method consists of socializing disaster material with the help of visual aids and direct simulations guided by the BPBD team. Through the stages of preparation, socialization, and simulation, students were given an in-depth understanding of the types of disasters, evacuation techniques, and the use of light fire extinguishers (APAR). The evaluation results showed a significant increase in understanding from 30% to 80% after this activity was implemented. This increase shows that disaster education involving theory and practice is effective in building students' awareness and preparedness. This program is expected to be continued regularly to build a culture of disaster preparedness among school students.